The Influence of a Serine Protease Inhibitor, Nafamostat Mesilate, on Plasma Coagulation, and Platelet Activation during Experimental Extracorporeal Life Support (ECLS) - Mellgren, Karin; Skogby, Maria; Friberg, Lars Göran; Tengborn, Lilian; Wadenvik, Hans (Thrombosis and Haemostasis, 1998)
Introduction: During extracorporeal circulation the contact between blood and the artificial surface of the circuit induces several changes in the hemostatic system. The objective of the present study was to assess the effect of a serine protease inhibitor – Nafamostat mesilate (FUT-175) – on coagulation and on platelets during experimental extracorpo-real circulation. Methods: Two identical Extra Corporeal Life Support (ECLS) circuits were primed with fresh, heparinized human blood and circulated for 24 h. FUT-175 was added to one of the paired circuits and the other was used as a control. The following FUT-175 concentrations were employed: (1) 7.1 mg/l/h, (2) 14.2 mg/l/h, (3) 14.2 mg/l/h + 85.5 mg given as an initial bolus, (4) 28.5 mg/l/h + 171 mg given as an initial bolus. Blood samples were collected from the circuits before the start of the perfusion and at 0.5, 1, 3, 12, and 24 h of perfusion, and analysed for platelet count, plasma betathromboglobulin ( -TG), platelet membrane glycoprotein (GP) Ib and GPIIb/IIIa expression, thrombin/ antithrombin III complex (TAT), prothrombin fragment 1+2 (F1+2), fibrinogen, D-dimer, and plasminogen activator inhibitor 1 activity (PAI-1). Results: Significantly higher platelet membrane GPIb expression and lower plasma -thromboglobulin levels were observed in the circuits holding FUT-175, suggesting a lower degree of platelet activation. Also, a reduced activation of the coagulation system was observed in the “FUT-circuits”, as reflected by the levels of F1+2 and TAT, and the PAI-1 activity that was rapidly inactivated. Conclusion: FUT-175 reduces the activation of platelets and plasma coagulation in an in vitro ECLS model.